Cocktails with a curator the Frick Collection - Salomon, Xavier F. 1979-; Ng, Aimee; Dalvit, Giulio (Rizzoli Electa, 2022)
Based on the critically acclaimed video series of the same name, Cocktails with a Curator is a collection of lively and informative essays. Paintings, sculpture, furniture, and porcelain--from medieval times through the glorious Renaissance to the early twentieth century--are discussed for their exemplary status. The creators are some of the greatest artists and include Rembrandt, Vermeer, Whistler, Manet, Velázquez, and Veronese, and the stories (of both artists and subjects) are tantalizing. Cocktails, with recipes, are thematically paired with the works: a Jaded Countess (absinthe, vodka, lemon juice, and simple syrup) with Ingres's portrait Comtesse d' Haussonville; a classic Pimm's Cup with Gainsborough's depiction of English beauty Grace Dalrymple Elliott; and a Bloody Mary (named after the last Catholic regnant queen of England) with Holbein's painting of Sir Thomas More, who opposed the Reformation of Mary's father, Henry VIII. The perfect addition to any art connoisseur's library, this book is an innovative and intoxicating way to enjoy the treasures of a world-renowned art collection.
Keywords: Serrano, Luis -- 1955-; Frick Collection; Zeichnung; Sammlung; Rezeption; Kunst; Kunstführer